German Economy Autumn 2024: Struggling to Gain Traction - Jens Boysen-Hogrefe; Dominik Groll; Timo Hoffmann; Nils Jannsen; Stefan Kooths; Christian Schröder; Nils Sonnenberg (Kiel Institute for the World Economy (IfW Kiel), 2024)
The German economy is not getting off the ground. The signs of a beginning recovery that were observable a few months ago have not materialized. Leading indicators now are signaling that economic output will continue to stagnate for the time being. The manufacturing industry is in recession and private households are holding back on consumption despite rising real incomes. Investments continue to suffer from the high level of uncertainty and restrictive financing conditions. GDP is likely to increase again slightly from next year. The restrictive impact of monetary policy is gradually easing. The continued rise in real incomes will lead to moderate increases in private consumption and the stable economic expansion of the world economy is likely to stimulate exports somewhat. Given the current low level of overall economic production, however, the recovery will remain weak. Overall, we have revised our forecast downwards. For the current year, we now expect GDP to decline by 0.1 percent (summer forecast: +0.2 percent), while next year it is likely to increase by 0.5 percent (1.1 percent). In 2026, GDP will probably increase by 1.1 percent, also supported by the higher number of working days, which will contribute 0.3 percentage points to the growth rate. Inflation has continued to fall and will probably be around 2 percent in the next two years. Unemployment will rise from 5.7 percent in 2023 to 6.1 percent in 2025 due to the weak economy. Demographic change will increasingly affect the labor market in the coming years and are expected to lead to a decline in employment in 2026. The budget deficit is likely to fall from 2.6 percent relative to GDP in 2023 to 1.7 percent in 2025, mainly due to the removal of the energy price brakes.
Keywords: 330